1999
DOI: 10.1038/sj.cdd.4400528
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB functions as both a proapoptotic and antiapoptotic regulatory factor within a single cell type

Abstract: Recently NF-kB has been shown to have both proapoptotic and antiapoptotic functions. In T cell hybridomas, both T cell activators and glucocorticoids induce apoptosis. Here we show that blockade of NF-kB activity, using a dominant negative IkBa, has opposite effects on these two apoptotic signals. Treatment with PMA plus ionomycin (P/I) results in the upregulation of Fas Ligand (FasL) and induction of apoptosis. Inhibition of NF-kB activity inhibits the P/I mediated induction of FasL mRNA and decreases the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 80 publications
(77 reference statements)
3
108
0
1
Order By: Relevance
“…In this context, NF-kB triggered the Fas-death cascade by directly activating the expression of Fas ligand (FasL) ( Duyao et al (1990), La Rosa et al (1994) et al, 1999; Lin et al, 1999;Zheng et al, 2001). The expression of a dominant IkB molecule (IkBaM) inhibited both FasL expression and apoptosis.…”
Section: Anti-and Proapoptotic Roles For Nf-kb In T Cellsmentioning
confidence: 99%
“…In this context, NF-kB triggered the Fas-death cascade by directly activating the expression of Fas ligand (FasL) ( Duyao et al (1990), La Rosa et al (1994) et al, 1999; Lin et al, 1999;Zheng et al, 2001). The expression of a dominant IkB molecule (IkBaM) inhibited both FasL expression and apoptosis.…”
Section: Anti-and Proapoptotic Roles For Nf-kb In T Cellsmentioning
confidence: 99%
“…31 Another report showed that activated NF-kB exhibited opposite functions following induction by different treatments in a single cell line; NF-kB activation induced by combined treatment with PMA and ionomycin was proapoptotic in a T-cell hybridoma cell line, whereas glucocorticoid-induced NF-kB was antiapoptotic in the same cells. 35 TNF/IFN-a induced a cytotoxic response in certain tumors, [18][19][20] and also had crosstalk interactions in immune responses. 36 We therefore investigated whether NF-kB activation induced by TNF/IFN-a, had an antiapoptotic or proapoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Interestingly, NF-kB can either induce or repress apoptosis in CD4 + CD8 + thymocytes, depending upon the nature of the activator. 21 In addition, its role in apoptosis may be dependent of the cell type, probably due to cross talk with other signals. The precise molecular mechanisms that determine the switch from an anti-to a pro-apoptotic role have not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%